Which is or should be the ideal level of participation of students of higher education in their own education? - Ortega-Mohedano, José; Rodríguez-Conde, Mª José (ACM International Conference Proceeding Series, 2020)
The global objective of this work is to contribute to the field of evaluation of the quality of higher education developed by higher education institutions (HEIs) from a multidimensional perspective, that considers all their activities, related to teaching, research, innovation and knowledge transfer. That is, any of the services offered by the universities (hereafter university will be considered as a synonym of a higher education institution - HEI). The work addresses the question, of how can we measure the quality of education offered by HEIs. And in particular, how to do it counting with the opinion of their main user: the student. Education is a type of service, and as such, educational institutions that offer it must try to satisfy the wishes and needs of users to whom it is addressed. Getting feedback from students about the origins of the quality of the higher education they receive should help towards reaching this goal. Therefore, it will be appropriate to define the quality of higher education from the perspective of the student. For this purpose, a multidisciplinary theoretical framework will be established, based on an approach, that conceives quality as meeting the needs and expectations of customers. Seeking to achieve the defined objective, we developed a solid theoretical framework, following the next stages of analysis. First, higher education was defined as a service. Second, the possible roles of the student of higher education were analyzed, particularly within the European Higher Education Area (EHEA). In this context, a new “continuum of student orientation” theoretical model of relations between the university and their students is proposed. Third, the concept of quality in higher education was defined, approaching it from the perspective of the student who perceives his/her service. Fourth, the "Gaps Model of Service Quality applied to higher education” framework was established. And fifth, the relationship between service quality and satisfaction in the field of higher education was addressed. This framework would serve later as foundation for the development of a measurement scale of the quality of service perceived by the student of higher education for both 'online' and 'off-line' services. Finally, including the above theoretical model in the mentioned framework, and considering the application of structural equation modelling for statistical methodology, causal relationships between latent variables and the existence of a moderating effect of the variable “student orientation to learning” is proposed.
Ponencia de la conferencia "6th International Conference on Technological Ecosystems for Enhancing Multiculturality, TEEM 2018; Salamanca; Spain; 24 October 2018 through 26 October 2018"
Keywords: online services; assessment; e-learning; higher education; quality of higher education; satisfaction; service quality; student orientation; Scopus(2); WOS(2)